Nominal groups in deaf and hearing students’ narratives: A functional perspective - Marsandi Manar (Universitas Pendidikan Indonesia, 2022)
Understanding the language aspect of deaf students in reference to their hearing counterparts plays a salient role in providing language teaching and learning treatment for the former. As the initial effort to contribute to the language pedagogy for individuals with deafness, this study reveals the patterns of nominal groups in the Indonesian narratives of four deaf senior high school students and four hearing students of the same level. A qualitative text analysis was adopted as the research design to investigate the nominal group patterns in both data sets. Eight narratives about “being chased by a dog” were first identified in terms of their schematic structure. Then the ‘things’ or ‘participants’ in the stories were analysed based on the experiential nominal group framework of Halliday and Matthiessen (2004), consisting of Deictic, Numerative, Epithet, Classifier, Thing, and Qualifier. The analysis of nominal group patterns shows that ‘participants’ in the four stories of deaf writers were most frequently represented with Thing only (76.9%), Thing + Deictic (17.9%), Thing + Qualifier (3.8%), and Thing + Epithet (1.3%). In the compositions of their hearing peers, five other patterns were also employed, including those with three constituents like Thing + Deictic + Qualifier. The findings of this study hint at the simplified nature of deaf students’ nominal groups. In narratives, complex nominal group patterns contribute to representing things specifically. It is expected that further treatment can be provided to assist deaf students in making meaning of their narratives functionally, for example, by using complex nominal group patterns.